On the Interplay of Motivational Characteristics and Academic Achievement: The Role of Need for Cognition - Anja Strobel; Alexander Strobel; Franzis Preckel; Ricarda Steinmayr (SAGE Publishing, 2024)
While intelligence and motivational variables are well-established predictors of academic achievement, Need for Cognition (NFC), the stable intrinsic motivation to engage in and enjoy challenging intellectual activity, has not yet been considered comprehensively in this field, especially not longitudinally. By applying latent change score modeling, we examined the incremental value of NFC, considering well-established motivational constructs and prior achievement in the prediction of academic achievement across different subjects in a longitudinal approach across two time points in a sample of secondary school students ( N T 1 = 271, N T 2 = 255). Correlations of NFC with grades were comparable to those of established predictors. NFC incrementally predicted academic achievement over and above prior achievement and ability self-concept. A mutual influence of NFC and academic achievement was found pointing to skill development as well as self-enhancement processes taking place in this interplay. Consequently, we propose to include NFC in models for the comprehensive explanation of academic achievement in school.